Dlaczego Kain? Motyw sacrum we wczesnych wierszach Marcina Świetlickiego - Grzeszna, Sylwia (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The article is a part of one chapter of a doctoral dissertation. I described the ways of using the motive of “sacrum” in literary works of poets debuting in the 1990s.Marcin Świetlicki, Tadeusz Różewicz as well as chosen by me Jacek Podsiadło refer in their poems to a modern formula of spirituality in which using the religious motives serves as a means of maintaining contact with a reader that is raised in particular tradition. In an analysis of Świetlicki’s literary works I take into consideration texts indicating the search of own discourse of one of the representatives of the so-called “BruLion” generation, as well as the possibility of religious conditioning of provocative gestures of the author of “Zimne Kraje.”